High-intensity circuit training for improving anthropometric parameters for women from low socioeconomic communities of Sikandarabad: A clinical trial - Mehmood, Sana; Khan, Amna; Farooqui, Sumaira; Zahoor, Al-Wardha; Adnan, Qurat Ul Ain; Khan, Usman (PLOS ONE, 2022)
Background An alarming trend of sustained physical inactivity has been observed among women in socioeconomically disadvantaged areas, mainly due to the lack of time and high cost of gym facilities. Although physical activity essentially contributes to disease prevention, evidence supporting time-efficient exercise on anthropometric measures is limited. This study aimed to identify the effectiveness of interval-based high-intensity circuit training (HICT) on anthropometric measures and the nature of the relationship between these measures. Methods A single-group, quasi-experimental study was conducted in the community park of Ziauddin Hospital at Sikandarabad. Sixty women who were overweight and had sedentary lifestyles were recruited for a six-week HICT-based program conducted at 85%–95% maximum heart rate (MHR) on every alternate day. Outcome measures were assessed at baseline and at 6-weeks including anthropometric parameters (body mass index [BMI], body fat percentage [BF%], and waist-to-hip ratio [WHR]). Results The six-week HICT-based program demonstrated a significant reduction in BMI (p<0.001), BF% (p<0.001), and WHR (p<0.001). Reductions in the BMI mean from 27.3±1.3 to 25.1±1.4 and BF% mean from 31.9±2.3 to 27.6±2.4 were observed following 18 sessions of HICT. The effect of age on BF% and WHR was linearly significant (p<0.001) with increasing age (BF%) and WHR. Conclusion Interval-based HICT was an effective exercise regimen for improving BMI, BF%, and WHR. Furthermore, the exercise protocol was feasible and well tolerated, with no reported adverse events, and it could be easily implemented in real-world community settings. BF% and WHR were significantly influenced by increasing age; therefore, our findings support the importance of exercise implementation, especially with increasing age, for the maintenance of a disease-free healthy lifestyle.